2015
DOI: 10.1016/j.mod.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific control of niche positioning and integrity in the Drosophila testis

Abstract: A fundamental question is how complex structures are maintained after their initial specification. Stem cells reside in a specialized microenvironment, called niche, which provides essential signals controlling stem cell behavior. We addressed this question by studying the Drosophila male stem cell niche, called the hub. Once specified, the hub cells need to maintain their position and architectural integrity through embryonic, larval and pupal stages of testis organogenesis and during adult life. The Hox gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Genetic analyses indicate that the Vav protein present in Drosophila melanogaster participates in Rac1-mediated axon guidance processes that contribute to both larval viability and the locomotor activity of adult flies [115,116]. This protein is also involved in an epidermal growth factor receptor-triggered signaling pathway that contributes to the viability of the male stem cell niche [117,118]. The use of gain-of-function Vav mutants has additionally revealed that this GEF can participate in several Rac1-dependent developmental processes in this fly such as dorsal closure, myoblast fusion, the proper migration of caudal visceral mesodermal cells, and the formation of the tracheal system [72].…”
Section: Physiological Rolesmentioning
confidence: 99%
“…Genetic analyses indicate that the Vav protein present in Drosophila melanogaster participates in Rac1-mediated axon guidance processes that contribute to both larval viability and the locomotor activity of adult flies [115,116]. This protein is also involved in an epidermal growth factor receptor-triggered signaling pathway that contributes to the viability of the male stem cell niche [117,118]. The use of gain-of-function Vav mutants has additionally revealed that this GEF can participate in several Rac1-dependent developmental processes in this fly such as dorsal closure, myoblast fusion, the proper migration of caudal visceral mesodermal cells, and the formation of the tracheal system [72].…”
Section: Physiological Rolesmentioning
confidence: 99%
“…In addition, in adult male D. melanogaster, Abd-B is required for correct function of the accessory gland (32), which is a component of the reproductive system that regulates the female response to mating (33). Moreover, this Hox gene is also required to maintain the identity of both germ line and somatic stem cells in the adult testis (34)(35)(36)(37). However, these somatic and postembryonic functions of Abd-B do not affect embryonic PGC establishment in D. melanogaster, which takes place much earlier in development.…”
Section: Significancementioning
confidence: 99%
“…In addition, in adult male D. melanogaster, Abd-B is required for correct function of the accessory gland (32), which is a component of the reproductive system that regulates the female response to mating (33). Moreover, this Hox gene is also required to maintain the identity of both germ line and somatic stem cells in the adult testis (34-37). However, these somatic and post-embryonic functions of Abd-B do not affect embryonic PGC establishment in D. melanogaster , which takes places much earlier in development.…”
Section: Introductionmentioning
confidence: 99%